Theoretical-experimental correlation of Voc in isoindigo-based small molecules for photovoltaic applications - O. Javier Hernández-Ortiz; Mario Rodríguez; Rosa Angeles Vazquez-García; Karina Alemán Ayala; María Aurora Veloz Rodríguez; Arián Espinosa-Roa; José-Luis Maldonado (Chemical Physics Impact)
A family of isoindigo derivatives (OII1-OII8) with D-A'-A-A'-D and D-A-D electronic architecture was designed and synthesized to study their optical and electronic properties for photovoltaic applications. These small molecules integrate isoindigo as an electron acceptor, cyano-containing π-bridges, and diverse donor groups, including triphenylamine, carbazole, and fluorene. The synthesis involved aldol condensation, direct arylation, and Suzuki coupling. Theoretical (DFT/TDDFT) and experimental analyses revealed intense absorption bands and tunable bandgaps (1.61–1.94 eV). Experimental validation of HOMO-LUMO levels and photovoltaic performance was conducted, with OSC devices achieving Voc values up to 0.73 V in preliminary studies. A strong correlation was observed between theoretical predictions and experimental electronic parameters for OII3 and OII4 with D-A'-A-A'-D architectures. This work demonstrates the potential of isoindigo-based molecules for organic solar cells.